2020
DOI: 10.1002/hed.26267
|View full text |Cite
|
Sign up to set email alerts
|

Heat and moisture exchanger cassettes: Results of a quality/safety initiative to reduce postoperative mucus plugging after total laryngectomy

Abstract: Background Tracheal dryness is a concern after total laryngectomy due to the potential for mucus plugs (MP). This study compared heat and moisture exchanger (HME) cassettes to external tracheal humidification (ETH) surrounding MP events. Methods A retrospective comparative cohort study comparing outcomes before/after implementation of a patient safety initiative utilizing HME during post laryngectomy hospitalization. The number of MP events were compared with a pre‐implementation control group using ETH. Patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(17 citation statements)
references
References 25 publications
0
15
2
Order By: Relevance
“…Our findings show that the majority of PTL (69%) included in the audit used a closed-system HME. While this is a lower proportion than has been quoted in previous studies 5 , HME usage varied across centres from 28% to 95%. The centre with the largest number of cases also reported the highest HME use, while many of those centres with lower HME use also reported higher levels of missing data.…”
Section: Discussioncontrasting
confidence: 66%
See 2 more Smart Citations
“…Our findings show that the majority of PTL (69%) included in the audit used a closed-system HME. While this is a lower proportion than has been quoted in previous studies 5 , HME usage varied across centres from 28% to 95%. The centre with the largest number of cases also reported the highest HME use, while many of those centres with lower HME use also reported higher levels of missing data.…”
Section: Discussioncontrasting
confidence: 66%
“…While closed system HMEs are more expensive than alternative stoma covers 3 , the benefits are well recognised including reduced coughing, shortness of breath, mucous production, plug formation and chest infections 5,6,7 . There is a correlation between duration of HME use and pulmonary benefit 8 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In total, 3 (30%) randomized controlled trials [ 28 , 29 , 40 ], 3 (30%) time-series studies in which patients acted as their own controls [ 31 , 41 , 42 ], 1 (10%) retrospective comparative cohort study [ 43 ], 1 (10%) retrospective clinical and survey study [ 12 ], 1 (10%) multigroup design study (study design was not reported by the authors themselves) [ 16 ], and 1 (10%) case-control study [ 44 ] were included. The new generation of HMEs were compared with a control (no HME use) [ 12 , 16 , 28 , 39 - 41 ], an external humidifier [ 29 , 43 , 44 ], or a previous generation HME [ 31 ]. The studies were performed in 7 different countries, namely the United States [ 16 , 43 ], Canada [ 44 ], France [ 29 , 40 ], Italy [ 41 , 42 ], Spain [ 31 ], the Netherlands [ 12 ], and Poland [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…The new generation of HMEs were compared with a control (no HME use) [ 12 , 16 , 28 , 39 - 41 ], an external humidifier [ 29 , 43 , 44 ], or a previous generation HME [ 31 ]. The studies were performed in 7 different countries, namely the United States [ 16 , 43 ], Canada [ 44 ], France [ 29 , 40 ], Italy [ 41 , 42 ], Spain [ 31 ], the Netherlands [ 12 ], and Poland [ 28 ]. The studies included a total of 550 patients, with a minimum of 30 patients [ 41 , 42 ] and a maximum of 89 patients [ 12 ].…”
Section: Resultsmentioning
confidence: 99%